The development of BEEM modeling for the characterization of Si/Ge self-assembled quantum dot heterostructures - Hutagalung, Sabar D.; Yaacob, Khatijah A.; Sakrani, Samsudi; Mat Isa, Ahmad R. (2006)

(untitled)
In this paper we present a ballistic electron emission microscopy (BEEM) modeling for the Si/Ge quantum dots characterization. BEEM is a new characterization technique by using electrons ejected from the scanning tunneling microscopy (STM) tip to investigate the metal-semiconductor interfaces. Because of the high resolution of the STM system, BEEM is promising in the characterization of quantum dots as the charge transport on individual dot can be characterized compared to the multitude of dots necessitated in other techniques. This method requires three terminals: a connection to the STM tip to inject electrons, a connection to the sample to collect electrons that traverse the interface, and a third grounding terminal. The energy and angular distribution of the injected electrons can be controlled by varying the tip potential. By using the characteristic data of the injected and collected electrons, many useful transport-related properties of the sample can be obtained. The silicon quantum dots (Si QDs) may be fabricated by taking advantage of the Stranski-Krastanov growth model. Germanium layer has been choosed as a barrier layer due to the large lattice mismatch between Si and Ge. The n-type Si(100) was oxidized to grow âˆ¼10 nm thickness of SiO2 layer. Hemispherical Si nanodot were self-assembled growth on an HF-treated SiO2 layer by LPCVD technique. The Ge layer were deposited on the pregrow silicon dot. Thin gold (Au) films cap can be used to provide a conductive layer on top of the Si QDs for the BEEM measurement. When the STM tip is positioned on the dot, the injected electron would experience a band profile similar to a double-barrier heterostructure, wherein the quantum dot act as the potential well. However, when the tip is positioned away from the dot (off dot), the injected charge would rather experience a potential step (single barrier) with the band profile.